Let My People Go! - Penny Frank; Tony Morris (UK USA Albatross Books Australia Lion Publishing, 1986)
Retells the Old Testament story of Joseph who was sold into slavery by his brothers and, because of his ability to interpret dreams, made a place for himself in the land of Egypt.
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Theology